Management of Primary and Recurrent Clostridium difficile Infection: An Update - Jocelyn Chai; Christine H. Lee (MDPI AG, 2018)
Background: Clostridium difficile infection (CDI) is one of the most common healthcare-associated infections (HAI) in the United States and Canada, and incidence rates have increased worldwide in recent decades. Currently, antibiotics are the mainstay treatments for both primary and recurrent CDI, but their efficacy is limited, prompting further therapies to be developed. Aim: This review summarizes current and emerging therapies in CDI management including antibiotics, fecal microbiota transplantation, monoclonal antibodies, spore-based therapies, and vaccinations.